a DESAIN HANDOUT STEAM@HOME BERBASIS TEAM BASE PROJECT PADA MATAKULIAH BIOTEKNOLOGI : DESAIN HANDOUT STEAM@HOME BERBASIS TEAM BASE PROJECT PADA MATAKULIAH BIOTEKNOLOGI - Sundari Sundari (Universitas Cokroaminoto Palopo, 2023)
Innovation efforts in the development of teaching materials have been carried out through development research procedures with the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation) in the Biotechnology course. This study aims to develop STEM-based handouts on the concept of Fermentation, determine the validity of STEM-based handouts based on the feasibility aspects of content, presentation, language, STEM and graphics, and determine user responses to STEM-based handout products. The results of this development indicate that STEM-based handouts are feasible to use with a feasibility assessment by experts of 83.61%. For user responses from 6th semester students of Biology Education Study Program, it is known that STEM-based handout products can be used in Biotechnology learning with a score of 73.71%. Recommendations from this research need to improve the design with STEM characteristics in technology and engineering aspects as well as more detailed mathematics.